Reading skills of daf teacher training students in german ınventory based on c-tests - HEPPINAR, GÜLAY (My University, 2022)
Measuring language proficiency is crucial in encouraging students of German Language Teaching programs designed for non-native German speakers to improve their language skills. The aim of this study is to identify how well the C-Test measures the reading proficiency in German of the students in the German Language Teaching programs in Turkey. For this purpose, the present study compared the German C-Test with another test for German as a Foreign Language: TestDaF. The sample for this study consisted of 133 students currently enrolled at the Department of German Language and Teaching at Marmara University in Istanbul. The results of these tests indicate that there is a correlation between the German C-Test and TestDaF. In addition, the results also clearly show that the students on the German language teaching programs need support in reading in German. This need for support not only applies to students who learned German exclusively in Turkish schools and educational establishments, but also those who have a migration background, i. e. who have experience of living in Germany. The study shows that the C-Test can be used as a diagnostic tool for measuring the reading proficiency of students of German language teaching programs at Turkish universities. The C-Test gaps, which are categorized by word, sentence and text criteria, enable us to identify the students\" reading skills and reading strategies. Moreover, the students can be classified as high-performing and low-performing students.
Keywords: DİL VE DİLBİLİM; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); DİLBİLİM; LANGUAGE & LINGUISTICS; ARTS & HUMANITIES; Arts & Humanities (AHCI); LINGUISTICS; Dilbilim ve Dil; Koruma; Dil ve Dilbilim; Sanat ve Beşeri Bilimler (çeşitli); Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Linguistics and Language; Conservation; Language and Linguistics; Arts and Humanities (miscellaneous); General Arts and Humanities; Social Sciences & Humanities